A validity and reliability study of the coping self-efficacy scale - Chesney, Margaret A. (2006)
OBJECTIVES: Investigate the psychometric characteristics of the coping self-efficacy (CSE) scale, a 26-item measure of one’s confidence in performing coping behaviors when faced with life challenges. DESIGN: Data came from two randomized clinical trials (N1 = 149, N2 = 199) evaluating a theory-based Coping Effectiveness Training (CET) intervention in reducing psychological distress and increasing positive mood in persons coping with chronic illness. METHODS: The 348 participants were HIV-seropositive men with depressed mood who have sex with men. Participants were randomly assigned to intervention and comparison conditions and assessed pre- and post-intervention. Outcome variables included the CSE scale, ways of coping, and measures of social support and psychological distress and well-being. RESULTS: Exploratory (EFA) and confirmatory factor analyses (CFA) revealed a 13-item reduced form of the CSE scale with three factors: Use problem-focused coping (6 items, α = .91), stop unpleasant emotions and thoughts (4 items, α = .91), and get support from friends and family (3 items, α = .80). Internal consistency and test–retest reliability are strong for all three factors. Concurrent validity analyses showed these factors assess self-efficacy for different types of coping. Predictive validity analyses showed that residualized change scores in using problem- and emotion-focused coping skills were predictive of reduced psychological distress and increased psychological well-being over time. CONCLUSIONS: The CSE scale provides a measure of a person’s perceived ability to cope effectively with life challenges, as well as a way to assess changes in CSE over time in intervention research.